Evolution of earnings and rates of returns to education in Mexico - Lápez-Acevedo, Gladys (Policy research working paper, 2001)
Inequality in education accounts for a large share of the inequality in earnings in Mexico. But the increase in earnings inequality does not appear to reflect a worsening in the distribution of education. The cause instead appears to be skill-biased technological change facilitated by increased economic openness